Tradisi Sijagaron pada Upacara Kematian Saur Matua di Kabupaten Toba - Robert Sibarani; Christina Rayani Panggabean (Journal of Language Development and Linguistics, 2022)
In this study the author discusses "the Sijagaron Tradition at the Death Ceremony of Saur Matua in Toba Regency".What Elements Are In Sijagaronnand How is Sijagaron's Dance and Hata-Hata Performance. This study aims to describe what elements are contained in Sijagaron, How is the performance of dances and dances of Sijagaron, How are cultural values ​​and norms in Sijagaron. The method used in this research is a descriptive qualitative method. and The theoretical basis used to analyze is the theory of oral tradition.